ANALYSIS OF PRODUCTION AND PROFITABILITY OF CHICKEN EGG FARMS IN ABIA STATE, NIGERIA - Sylvanus Ibeabuchi OGBONNA; Christopher Ogbonna EMEROLE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was to analyze Production and profitability of Chicken Egg farms in Abia State Nigeria . Primary data gathered with structured questionnaire from 120 chicken egg producing farms were analysed with descriptive and inferential techniques (frequency distribution Tables, mean, standard deviation, farm budget and Ordinary least square regression). In terms production characteristics, 51.7% of the farms had existed for at least 10 years, with 45.8% of them located in semi-urban areas, operating with staff strength of 1-5 persons with mean monthly pay of N10,000.00. The mean annual production estimates revealed that the farms incurred annual cost (variable and fixed) of N33,602,206.0 and earned mean annual net profit of N18,757,794.0. Profitability of chicken egg production was highly determined by location of the farm, level of education of the manager, use of paid labour, and interest paid on borrowed funds; but moderately influenced by age of the farm manager, total eggs produced, cost of feeds consumed by the birds, and production experience of the manager. We recommended strict enforcement of disbursement of low interest livestock loans, and setting up of chicken egg production clusters managed by educated and experienced managers by farmers and Abia State Government.